LEGAL CHALLENGES OF SUPPLY CHAIN DUE DILIGENCE LAWS DALAM PERDAGANGAN INTERNASIONAL KONTEMPORER - Akhmad Faishal; Annie Myranika; Bachtiar Kemal Harahap; Asri Cahyadi; Teddy T Pingak; Dian Retno Widayati (CV. Lafadz Jaya, 2026)
The increasingly complex development of international trade has driven the emergence of various supply chain due diligence (SCDD) regulations at the regional and international levels. Regulations such as the German Supply Chain Due Diligence Act (LkSG), the French Duty of Vigilance Law, and the proposed European Union Corporate Sustainability Due Diligence Directive (CSDDD) pose significant legal challenges for business actors, particularly in developing countries. This study analyzes the main legal challenges faced in implementing SCDD laws, including aspects of jurisdiction, extraterritoriality, standard harmonization, compliance burdens for Micro, Small and Medium Enterprises (MSMEs), and implications for the economic sovereignty of developing countries. The research method used is normative juridical with a comparative law analysis approach and document study. The results show that SCDD laws create a fragmented legal landscape that requires multilateral coordination mechanisms, special protection for MSMEs, and differentiated responsibilities approaches to ensure regulatory effectiveness without hindering developing countries' participation in global trade.